IMF Staff papers : Volume 33 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1986)
WILLIAM. white, who joined the International Monetary Fund in 1948, spent his entire professional life in the Research Department. Present and past staff members, many of whom benefited from his advice, have asked that his contribution-to the work of the Fund should receive recognition in Staff Papers. This appreciation draws on excerpts from written recollections of some of his colleagues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Banking; Monetary Policy; The Supply Of Money and Credit